PERFORMA PERTUMBUHAN DAN KETAHANAN STRES STADIA AWAL UDANG GALAH Macrobrachium rosenbergii YANG DIBERI Bacillus sp. - Munti Yuhana; Darna Andrian Ramadhan; Hary Krettiawan; Usamah Afiff (Jurnal Teknologi Perikanan dan Kelautan, 2021)
The study aimed to evaluate the effect of the water application of probiotic Bacillus sp. DMP13 on the growth and stress response of giant freshwater prawn larvae Macrobrachium rosenbergii. The larvae used in this experiment were 1-day-old larvae post-hatching with an average body weight of 2.7±0.6 mg and an average length of 2.1±0.1 mm. The larvae were reared in 2 L plastic tanks with a density of 100 L-1 for 21 days. The study was conducted using 4 treatments with three replications of each, namely A (control without probiotic), B (Bacillus sp. DMP13 with cell concentration of 102 CFU (colony forming unit) mL-1), C (Bacillus sp. DMP13 with 104 CFU mL-1) and D (Bacillus sp. DMP13 with 106 CFU mL-1). Probiotic was applied in the rearing media on days 9th up to 18th with 3 days intervals. The results showed that application of Bacillus sp. DMP13 with a cell density of 102 CFU mL-1 was able significantly increased the absolute larvae weight (29.67±1.88 mg), increased larval survival in stress concentrations of 1,250 μL L-1 of formalin solution (the highest larval survival rate 98.3±2.9%). Treatment with 102 CFU mL-1 probiotic cell addition also increasing the total bacterial viable count in the media (the cell density reached 5.99±0.28 log CFU mL-1). However, other parameters such as the larvae stage index, survival rate, and absolute length of the larvae with probiotic treatments were not significantly different from those of control.